Kualitas Papan Komposit dari Sekam Padi dan Plastik HDPE Daur Ulang Menggunakan Maleic Anhydride (MAH) sebagai Compatibilizer - Fathanah, Umi (Jurnal Rekayasa Kimia & Lingkungan, 2011)
The utilization of rice husk as raw material on preparation of composite board could be used as alternative and cheap construction material. In this research, the composite board was prepared by mixing fined rice husk, recycledhigh density polyethylene (HDPE) plastic. Maleic Anhydride (MAH) was added ascompatibilizer. The objective of this research is to develop an alternative and a cheap technologyon fabrication of composite board by utilizing rice husk waste as filler and plastic from the type of recycled HDPE plastic as matrix. In order to improve the compactness of rice husk and recycled HDPE plastic thus the addition of MAH as compatibilizer is carried out. The research aspect learned is the MAH addition variation as much of 4% and 8% from HDPE plastic weight, and the mixing ratios of filler and matrix which are 30:70; 40:60; 50:50; 60:40; 70:30. Casting process of the homogonized solution was carried out at casting temperature of 145oC for 20 minutes. The research result obtained indicates that the value of composite board density has fulfilled standard of SNI 03-2105-1996. The maximum water adsorbtion is obtained on composition of filler and matrixof 60:40 where with the addition of MAH 4% and 8% they are 10,1% and 6.9%, respectively. The addition of MAH as much of4% and 8% has resulted composite board with tensile strength value that has fulfilled SNI standard. Whereas the addition of MAH as much of 8% could increase modulus of rapture value of composite board i. e. 82.5 85.2 kgf/cm2and they have fulfilled standard of SNI 03-2105-1996.Keywords: Composite board, Maleic Anhydride (MAH), Recycled HDPE plastic, Tensile Strength, modulus of rapture.